Google Jam board as a possible solution for e-learning in preschool - Boltá Hidalgo, María (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The purpose of this article is to explain some of the barriers that preschool teachers can face when they are trying to implement ICT resources in their classes. At the same time, we will suggest some ideas to overcome them as well as examples of different activities developed at CEIP San Fernando, a public school in Tenerife, Spain. Although they are about prehistory, they can be applied to many different themes. Also, some can be used on different devices, like tablets in case of an online learning environment for a lockdown due to Covid-19 situation. Another topic that we will be focusing on is the use of physical resources that complement the digital experience.